A Mad King in a Mad World: The Death of Cambyses in Herodotus - Mcphee, Brian D. (Histos, 2018)
This paper advances a theological interpretation of the madness, downfall, and death of the Herodotean Cambyses, understood as divine retribution for the king’s slaying of Apis, the supreme violation of Egyptian nomoi. The first section defines the scope of Cambyses’ punishment more expansively than previous scholarship, from Smerdis’ murder to Cambyses’ anguished final days of restored sanity. The second section analyses Cambyses’ unusual variety of madness as a sort of ‘hyper-rationality’ that, ironically, blinds the mad king to the ‘madness’ of the world. The king’s ruin ultimately proves the moral of the Cambyses logos, that it is madness to deride nomoi, no matter how laughable they might appear.